Characterization study of inggu (ferula asafetida) resin - Zulkply, Siti Mariam; Mohamed, Farahidah; Mohd Shafri, Mohd Affendi (2014)
Pre-formulation study is the main phase of drug development. At the early stage of pre-formulation study, characterization has a significant role in determining the physical and chemical properties of a drug candidate. The physicochemical parameters conducted in this study were determination of pH, particle size analysis and solubility test in different type of solvents. Results of the determination of pH showed (pH of 5.69) indicating acidic. In particle size analysis, the numerous distribution of resin was 5.58% (highest peak) where the particle’s diameter range from 105.24µm to 117.13µm. The resin was slightly soluble in hot water, but insoluble in other solvents for the solubility test. This exact identification could elucidate the physical and chemical composition present in Inggu.